PEDAGOG KADRLARDÍ TAYARLAWDA KÁSIPLIK ETIKANÍŃ ORNÍ HÁM ÁHMIYETI - Muratbaeva, A.J. (SCIENCE and SOCIETY, 2025)
The article examines the significance of professional ethics in the training of pedagogical personnel. The author reveals the features, purpose and objectives of pedagogical ethics, the moral and legal foundations of ethical requirements for the teacher's personality. The article also focuses on the axioms that every teacher should take into account in their professional activities.
Keywords: professional ethics; pedagogical ethics; professional honor; professional pride; pedagogical duty; personal morality; responsibility; self-improvement; teacher status